Incidencia de los huertos comestibles en indicadores de sostenibilidad en la comunidad San Pablo de Tarugo, Canuto - Bazurto Zambrano, Selena Monserrate (2023)
The present investigation was developed in the San Pablo de Tarugo community in Canuto parish, Chone canton; whose objective was to evaluate the incidence of edible orchards in sustainability indicators in the community under study. For this purpose, indicators were applied to determine the initial sustainability level in the site, by recognizing the study area and subsequent application of the sustainability barometer with scales of: bad-unsustainable (0-20), poor-almost unsustainable (21-40), medium-intermediate (41-60), adequate-almost sustainable (61-80) and good-sustainable (81-100). Likewise, edible orchards (cucumber, pepper, chives, coriander and tomato) were implemented as a sustainability strategy at the San Pablo de Tarugo site, with the respective pest control. Finally, the level of post-strategy sustainability in the community was measured, the sustainability barometer was applied again. The results obtained show that, initially, the area converted to organic farming in the community was 2.2% determined as unsustainable; while, after the strategy, this was 41.21%, being at a medium-intermediate level. On the other hand, regarding the initial knowledge of the population, this was 9.33, which means that they were regular; meanwhile, knowledge after the strategy was 12.5, considered good; according to the scale established for this purpose. In conclusion, the change in the sustainability of the San Pablo de Tarugo community post-strategy was evidenced, demonstrating the sustained development and citizen well-being that can be achieved with the implementation of good environmental practices.